Methods of interpreting homemaking education - Marcum, Ruth, author; Morgan, David H., advisor; Williamson, Maude, advisor; Hamilton, Olive F., committee member; Kinyon, Kate Pamela Woodard, 1881-, committee member (Colorado State University. Libraries, 1945)
To view the abstract, please see the full text of the document.
Keywords: Home economics -- Oklahoma; Home economics -- Study and teaching